2020
DOI: 10.1007/978-981-15-4814-7_1
|View full text |Cite
|
Sign up to set email alerts
|

Current Insight into the Novel Coronavirus Disease 2019 (COVID-19)

Abstract: SARS-CoV-2 is a novel strain of coronavirus that has not been previously identified in humans. It has been declared a pandemic and has infected at least 1,844,683 individuals and caused 117,021 deaths as of 14th April 2020. Transmission among humans occurs via close contact with an infected individual that produces respiratory droplets. Patients have been shown to undergo acute respiratory distress syndrome, which is defined as cytokine storm. The diagnosis relies on detection of nucleic acid, IgG/IgM antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
0
25
0
3
Order By: Relevance
“…Up-to-date studies revealed that, though SARS-CoV-2 and SARS-CoV identify a similar receptor (ACE2) in humans ( 194 , 196 ), there is a noteworthy variation in the antigenicity between SARS-CoV and SARS-CoV-2 which has significance on the development of therapeutic options against this rapidly emerging virus ( 197 ). The SARS-CoV-2 spike protein exhibits a higher affinity to the ACE2 receptor in comparison to SARS-CoV, but hACE2 showed a lower binding affinity to RBD (Receptor Binding Domain) of SARS COV-2 when compared to SARS CoV ( 194 , 198 ). The two most paramount enzymes of SARS CoV-2, proprotein convertase furin- potentiates cell fusion and serine protease TMPRSS2, are responsible for S-protein activation and are propitious drug targets for the treatment of COVID ( 180 , 194 , 199 ).…”
Section: Major Drug Targets Of Sars Cov-2mentioning
confidence: 99%
See 1 more Smart Citation
“…Up-to-date studies revealed that, though SARS-CoV-2 and SARS-CoV identify a similar receptor (ACE2) in humans ( 194 , 196 ), there is a noteworthy variation in the antigenicity between SARS-CoV and SARS-CoV-2 which has significance on the development of therapeutic options against this rapidly emerging virus ( 197 ). The SARS-CoV-2 spike protein exhibits a higher affinity to the ACE2 receptor in comparison to SARS-CoV, but hACE2 showed a lower binding affinity to RBD (Receptor Binding Domain) of SARS COV-2 when compared to SARS CoV ( 194 , 198 ). The two most paramount enzymes of SARS CoV-2, proprotein convertase furin- potentiates cell fusion and serine protease TMPRSS2, are responsible for S-protein activation and are propitious drug targets for the treatment of COVID ( 180 , 194 , 199 ).…”
Section: Major Drug Targets Of Sars Cov-2mentioning
confidence: 99%
“…For example, the repurposing drugs, including favipiravir, remdesivir, lopinavir, ritonavir, nebulized α-interferon, chloroquine, hydroxychloroquine, ribavirin, and interferon (IFN), have been shown to be effective for the treatment of COVID-19. Apart from this, some therapeutics are in clinical trials, such as peptide vaccine (mRNA-1273) ( 198 ) and antibody therapies ( 205 ). Recently, plasma therapy showed promising results for COVID-19 treatment ( 206 , 207 ).…”
Section: Psms Can Be Effective Over Synthetic Drugs Against Sars Cov-mentioning
confidence: 99%
“…SARS‐CoV‐2, the highly infectious agent responsible for the COVID‐19 pandemic, is a novel coronavirus that utilizes a glycosylated spike protein to enter human cells via the angiotensin‐converting enzyme 2 (ACE2) receptor. The lung is a primary site of entry for SARS‐CoV‐2, as evidenced by massive pulmonary inflammation and development of acute respiratory distress syndrome (ARDS) 1 . These changes frequently result in a cytokine storm that contributes to diffuse alveolar damage, alveolar capillary leakage, severe hypoxaemia, intense pulmonary oedema and pulmonary fibrosis 2…”
Section: Introductionmentioning
confidence: 99%
“…However, each country has its issues that the placing authority has to adjust the guidelines and protocols for the reality of each country or district. Thus, all nation has to prepare a COVID-19 Country Preparedness and Response Plan (CPRP) against the COVID-19 [27]. These CPRPs need constant monitoring and reviewing using indicators shared by WHO and CDC, for example, updating as the situation evolves.…”
Section: Pandemic Preparednessmentioning
confidence: 99%
“…Saxena, 2020 [27] reported that the success against a pandemic is grounded in the following actions, which have to be included in the protocols and guidelines: (i) Surveillance of the pathogen: characterization, epidemiology, transmission, symptoms, pathogenesis, diagnosis and detection, infection, contact tracing, data from confirmed cases, predicting mass infection outbreak, keeping a count, and estimation of mortality. (ii) Response management: production and supply of protective/preventive pharmaceutical interventions or nonpharmaceutical interventions; extensive test the community, education of the community about the disease and how it spreads, transmit and all information about the disease.…”
Section: Pandemic Preparednessmentioning
confidence: 99%